Elephantine, Ägypten. Gesamtprojekt Elephantine und Teilprojekt Lebenswirklichkeiten (Realities of Life). Die Arbeiten des Jahres 2016 bis Sommer 2017 - Sigl, Johanna (e-Forschungsberichte des DAI, 2017)
The temple of Satet, its reconstruction and the building of the so-called Annex Museum to house the finds from its excavations can be counted as one of the major achievements of the DAI in its last 50 years of work on Elephantine Island. The current project “Realities of Life” will provide the basis of a new exhibition concept for the Aswan Museum. The teaching program for local colleagues on modern archaeological methodology will rely not only on this museum and the ongoing excavation work, but was provided with an infrastructural background through the renovation of the excavation house of the institute on site.